Herbal remedies for male infertility and spermatogenic activity in animals: A review - GANGWAR, CHETNA; KUMARESAN, GURURAJ; MISHRA, ANIL KUMAR; KUMAR, ASHOK; POUROUCHOTTAMANE, R; RAI, BHUVANESHWAR (The Indian Journal of Animal Sciences, 2023)
Male infertility is becoming an important untouched area that needs immediate attention due to the increasing demand for breeding strategies, keeping in view the production and increasing per animal productivity. Many additives and antioxidants have been tried for enhancing the seminal quality, but still there is no evidence of full- proof effect on the conception rates in female animals. However, herbal preparations which promise multi-factorial effect in the breeding male animals can be explored, and in turn could prove to be a better tool to encounter the problem of male infertility holistically. The herbal preparations and its effect at the cellular, molecular and metabolic level still needs to be understood. However, the advantage of using the herbal ingredients could be, use of available local herbal ingredients which are more economical, affordable, can reduce the use of hormonal therapy, have less side effects on long term usage, and have greater acceptability by the farmers. These herbal ingredients will be useful in breeding programmes for improvement of germplasm in terms of productivity. The current review covers how the herbs can be utilized in improving the semen quality and quantity, enhancing function of sertoli and leydig cells, mating behaviour, fecundity, seminal antioxidant status, hypophyseal adrenal gonadal axis cum endocrine regulation, microcirculation of testes, as well as in semen cryopreservation and post thaw quality of different species.